Nursing Care for Sickle Cell Disease: A Comprehensive Review - Zainab Saleh Al ayesh et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Sickle Cell Disease (SCD) is a hereditary blood disorder characterized by abnormal hemoglobin that leads to distorted red blood cells, causing severe pain, organ damage, and increased risk of infection. Effective nursing care is crucial for managing SCD, addressing both acute complications and long-term health maintenance. This review explores the multifaceted role of nurses in the care of patients with SCD, including pain management, hydration therapy, infection prevention, patient education, and psychosocial support. By providing comprehensive and empathetic care, nurses play a vital role in improving the quality of life and clinical outcomes for individuals with SCD. Keywords: Sickle Cell Disease, Nursing Care, Nurses. Received Date: June 22, 2024 Accepted Date: July 22, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/174 DOI: https://doi.org/10.5281/zenodo.13174988